PENGARUH KEPEMIMPINAN AUTENTIK DAN KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KETERLIBATAN KERJA DENGAN EFIKASI DIRI SEBAGAI VARIABEL MEDIASI - Qori Al Banin; Nurul Farizal (Fakultas Ekonomi, 2026)
Work engagement is a positive psychological state reflected through enthusiasm, dedication, and full commitment to work. Previous research has shown inconsistent results regarding the influence of authentic leadership on work engagement. Some studies have found a positive influence, while others have shown the opposite results. Given this inconsistency, this study aims to examine the influence of authentic and transformational leadership on work engagement, with self-efficacy as a mediating variable. The research was conducted at RSUD Bumiayu using a quantitative approach with disproportionate stratified random sampling. Data were collected through questionnaires and analyzed using SEM-PLS with SmartPLS. The results indicate that authentic and transformational leadership positively influence self-efficacy and work engagement, and self-efficacy was found to mediate the influence of both leadership styles. These findings contribute theoretically to the work engagement model and provide practical recommendations for hospital management.